Corrosion resistance enhancement for low carbon steel by gas phase coating / Sameer K. Fayyadh and Faras Q. Mohammed - K. Fayyadh, Sameer; Q. Mohammed, Faras (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Corrosion Resistance Enhancement for low carbon steel is very important to extend its life service, the coating process is one of the methods which can using to achieve this, and it's the most important in surface treatments to improve the properties of metals and alloys surfaces such as corrosion resistance. In this work, low carbon steel was nitrided and coated with nano zinc using gas phase coating technical, to enhance the resistance of corrosion. The process included adding two layers. The first, a nitride layer, was added by precipitating nitrogen (N) gas, and the second, a zinc (Zn) layer, was added by precipitating Zn. The process of precipitating was carried out at different periods (5, 10, and 15 minutes). Scan electron microstructure (SEM), X-ray diffraction (XRD) and corrosion tests were carried out. The SEM and XRD results showed a new microstructure with the emergence of new phases (C3N4, Zn(N3)2, and γN). Also, the results of the corrosion test showed a significant improvement in corrosion resistance through a reduction in the corrosion rate (CR) and corrosion current density (icorr) which reached (1.598x10-3 mmpy) and (1.422x10-7 Amp/cm2 ) respectively, for coated samples, compared with 1.803×10-1 and 1.604x10-5 , respectively, for the base metal. also found an appreciable increase in corrosion protection efficiency (CPE), which reached 99.11%.